Augmented Reality-Based Learning for Tidal Flood Mitigation in Early Childhood Education: An ADDIE-Based Development Study - Handayani, Oktarina Dwi; Tri Tamiyati, Annisa (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Flood disaster preparedness education for early childhood remains a global challenge, especially in coastal communities facing flood threats in North Jakarta. Although the literature acknowledges the need for crisis mitigation education in early childhood, there remains a significant gap in the development of child-friendly, technology-integrated learning media. This study addresses this gap by developing MITBAR (Mitigasi Bencana Banjir Rob), an Augmented reality-based learning medium designed to improve the cognitive abilities and general knowledge of children aged 5 to 6 years. The research employed a research and development approach using the ADDIE model, encompassing needs analysis, instructional design, prototype development, implementation, and evaluation. The developed media integrates an AR mobile application with print-based materials that present comprehensive content on definitions, causal factors, impacts, and stages of disaster mitigation. Expert validation demonstrated high effectiveness across material experts (N Gain = 1.0), technology experts (0.96), language experts (0.92), and educator practitioners (0.91 to 0.87). Field testing conducted in a kindergarten in North Jakarta, involving five children in a small-group trial and sixteen children in a larger implementation stage, showed substantial improvements in conceptual understanding, with N-Gain values exceeding 0.79 and categorized as highly effective. These findings indicate that Augmented Reality can effectively transform abstract disaster preparedness concepts into experiential learning appropriate for early childhood contexts. Beyond the local setting, this study contributes to broader debates on immersive technology in early childhood disaster education by offering a developmentally grounded, systematically validated AR-based instructional model applicable to flood-prone coastal regions globally. However, the study is limited by its small sample size and short-term evaluation period, and it focuses primarily on cognitive outcomes. Future research is recommended to employ longitudinal designs and examine affective, behavioral, and long-term preparedness outcomes.